PENGARUH KOMPETENSI, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. BHANDA GHARA REKSA (PERSERO) KABUPATEN GIANYAR - I Wayan Pegi Andika; I Ketut Setia Sapta; I Gede Rihayana (VALUES, 2022)
The company will certainly create a strategy to be able to better satisfy its visitors on the one hand and on the other hand can improve the performance of its employees. For this reason, the role of competence, work discipline and motivation by employees is needed so that it is important for companies to retain these potential employees. This study aims to determine empirically the effect of competence, work discipline and motivation at PT Bhanda Reksa (PERSERO) Gianyar Regency. The population used in this study were all employees of PT Bhanda Reksa (PERSERO) Gianyar Regency, amounting to 36 people. The sampling technique used is a saturated sample or census, namely sampling that takes into account the consideration that the entire population is the sample. The analysis technique used in this research is multiple linear regression analysis technique. Prior to the analysis, the test was carried out first and continued with the classical assumption test consisting of the normality test, multicollinearity test, and heteroscedasticity test. The results showed that competence had a positive and significant effect on employee performance, work discipline had a positive and significant effect on employee performance, and motivation had a positive and significant effect on employee performance at PT Bhanda Reksa (PERSERO) Gianyar Regency.